Assessment of heavy metals among auto workers in metropolitan city: a case study - Khan, Kaleem; Room, Shahzada Amani; Bacha, Aziz-Ur-Rahim; Nabi, Iqra; Ahmad, Shabir; Younas, Muhammad; Ullah, Zahid; Iqbal, Akhtar; Alrefaei, Abdulwahed Fahad; Almutairi, Mikhlid H.; Chang, Jung-Wei; Chi, Kai Hsien (Frontiers in Public Health, 2023)
In recent decades, heavy metals (HMs) have emerged as a global health concern.Unfortunately, in Pakistan, there is a general lack of awareness regarding the potential health risks associated with HMs pollution among automobile workers. Herein, we investigated the concentration of heavy metals such as lead (Pb), cadmium (Cd), and chromium (Cr) among automobile workers who were occupationally exposed in Mingora City, Khyber Pakhtunkhwa, Pakistan. Three different automobile groups i.e., battery recyclers, spray painters, and mechanics were studied in detail. A total of 40 blood samples were collected from automobile workers groups while 10 blood samples were collected as control individuals from different locations in the study area. We investigated heavy metals concentration with a standard method using an atomic absorption spectrometer AAS (PerkinElmer Analyst 700, USA). Based on our findings, the battery recycling group displayed the most elevated Pb levels (5.45 ± 2.11 µg/dL), exceeding those of both the spray painters' group (5.12 ± 1.98 µg/dL) and the mechanics' group (3.79 ± 2.21 µg/dL). This can be attributed to their higher exposure to Pb pollution resulting from the deterioration, dismantling, grinding, or crushing of old batteries. In the context of chromium (Cr) exposure, a similar trend was observed among the battery recycling group, as well as the spray painters and mechanics groups. However, in the case of cadmium (Cd), the mechanics' group exhibited the highest level of exposure (4.45 ± 0.65 µg/dL), surpassing the battery recycling group (1.17 ± 0.45 µg/dL) and the spray painters' group (1.35 ± 0.69 µg/dL), which was attributed to their greater exposure to welding fumes and other activities in their workplace. We believe that our findings will encourage regulatory measures to improve the health of automobile workers. However, further work is needed to determine various health-related issues associated with heavy metal exposure among automobile workers.